2014
DOI: 10.21897/rmvz.87
|View full text |Cite
|
Sign up to set email alerts
|

Association of the bovine growth hormone gene with Holstein cattle reproductive parameters

Abstract: Objective. To determine the association of intron 3 polymorphism of the bovine growth hormone (BGH) gene, with age at first service, first birth, first postpartum service and second birth in a population of Holstein cows in the state of Antioquia. Materials and methods. The study was conducted on 408 Holstein cows in 8 herds. Genotyping was performed using PCR-RFLP technique with DNA extracted from peripheral blood by the salting out technique. The Phenotypic information used was collected for 4 years, from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…To date, few studies have investigated the effect of GH-MspI polymorphism on reproductive traits of bulls, and the results of these studies have reported a significant association between GH-MspI polymorphisms and the following sperm quality traits in bulls: fresh sperm motility, sperm concentration, minor and major defects, scrotal circumference and testicular growth after puberty (Lechniak et al, 2002;Una-nian et al, 2002;Gorbani et al, 2009); the reproductive traits of beef cattle have also been studied (Anggraeni et al, 2017). Arango et al (2014) reported that MspI polymorphism is associated with age at first service, first birth, first postpartum service and second birth. Furthermore, the MspI (+/+) genotype had the greatest effect on the age at first service and was considered the optimal genotype for reducing age at first service, first birth, first postpartum service and second birth.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have investigated the effect of GH-MspI polymorphism on reproductive traits of bulls, and the results of these studies have reported a significant association between GH-MspI polymorphisms and the following sperm quality traits in bulls: fresh sperm motility, sperm concentration, minor and major defects, scrotal circumference and testicular growth after puberty (Lechniak et al, 2002;Una-nian et al, 2002;Gorbani et al, 2009); the reproductive traits of beef cattle have also been studied (Anggraeni et al, 2017). Arango et al (2014) reported that MspI polymorphism is associated with age at first service, first birth, first postpartum service and second birth. Furthermore, the MspI (+/+) genotype had the greatest effect on the age at first service and was considered the optimal genotype for reducing age at first service, first birth, first postpartum service and second birth.…”
Section: Discussionmentioning
confidence: 99%
“…However, especially because of extensive production system in water buffalo in Turkey, it was not possible to have data for milk or meat yield. Arango et al (2014) identified the significant association of genotypes at the BGH-MspI locus with age at first service, first postpartum service, and first and second births in Holstein cows in the Antioquia province. Amiri et al (2018) showed a significant effect of the GH-AluI on the calving interval and the days open.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly Beauchemin et al (2006) has reported that effects of MspI polymorphism were not found in Brahman cattle and Nellore cattle population (Cardoso et al, 2014). On the contrary, Unanian et al (2000) reported that MspI polymorphism effects on the growth traits in Nellore cattle population and describes a significant effect on the average daily gain (ADG) from weaning at 15 months with DD genotype (equivalent with MspI-/-) and weight at first estrus and first calving in heifers in Holstein cattle (Arango et al, 2014). For the other SNP of GH in cattle, Reis et al (2001) reported that genotype LV of Portuguese cattle breeds have weight live higher than LL and VV in mature weight.…”
Section: Genotype Analysis Of Gh Gene Inmentioning
confidence: 99%